Application of artificial intelligence in the teaching and learning of mathematics: Implication for achievement and retention - Ogoke, Chinemeze James; Anyanwu, Anthony; Okolie, Alfred; Onuoha, Ekele; Vivian, Donald-Ozuzu (S&Co Publishing, 2025)
Advances in technology, particularly artificial intelligence (AI), offer opportunities to enhance teacher-student communication and improve learning outcomes in mathematics. This study investigates the impact of AI integration in mathematics education on student achievement and retention. The population comprised of 4204 Senior Secondary Three (SS3) in Owerri Municipal Council of Imo state Nigeria. A randomized controlled trial design was employed, with pre- and post-testing of 72 sample students selected through stratified simple random sampling and purposive sampling from a private school in Owerri, Imo State. The Mathematics Aptitude Test (MAT) was used to assess student learning, with a reliability coefficient of 0.74. Descriptive statistics and Analysis of Covariance (ANCOVA) were used to analyze the data. The results show that students who learned geometry with AI did not outperform those who learned without AI. Moreover, the retention rate of students taught without AI was higher. No significant differences were found in achievement and retention rates between boys and girls learning geometry with AI. These findings suggest that teachers and students should explore effective ways to leverage AI in mathematics education. Based on the findings, it was recommended that researcher recommended that activity-based classroom should be encouraged in the teaching and learning of mathematics, the use of AI in the teaching and learning of mathematics in secondary schools should be done under closed monitoring, and that improved technologies should be provided for both teacher and students for effective application of AI.